Analysis of Tabarru` Principle in Takaful Contract: Malaysian Experience - Ab Rahman, Asmak; Mohamad, Shamsiah (2010)
Under Shariah law, conventional insurance is prohibited due to the elements of gharar, maysir and riba in its implementation. Instead, takaful was introduced to replace conventional insurance. In order to ensure that takaful operates within Shariah law, a takaful contract is developed based on the concept of tabarru`. Although the takaful industry has been around for the past 26 years in Malaysia, the type of contract that should be applied in the creation of a tabarru` account has yet to be specified. The types of contracts that can potentially be used include those created based on the principles of hibah, waqf, sadaqah or any other similar tabarru`contracts. This paper argues that tabarru` contracts should use the sadaqah principle. This argument is based on the nature of the sadaqah principle which does not have strict requisites and conditions, unlike other tabarru` contracts. After suggesting the use of the sadaqah principle, this paper analyses ways in which sadaqah can be applied in the takaful contract. The use of the sadaqah principle to create tabarru` accounts, thus eliminating elements of interest, uncertainty and gambling is the central argument addressed in this paper. Keywords: takaful, tabarru`, sadaqah, Islamic finance, Islamic insurance